2023
DOI: 10.3389/fimmu.2023.1113607
|View full text |Cite
|
Sign up to set email alerts
|

Nutrients and rheumatoid arthritis: From the perspective of neutrophils

Abstract: Neutrophils are considered as core immune cells involve in the early stage of rheumatoid arthritis (RA) and participate in the disease progression. The underlining mechanisms include the elevated chemotaxis and infiltration of neutrophils, the increase in the reactive oxygen species and the promotion of neutrophil extracellular traps formation. Accumulating studies demonstrated the important role of nutrients intake played in the initiation and progression of RA. This study summarized the effects of several ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 75 publications
1
4
0
Order By: Relevance
“…RA in ammation causes changes in the structure of HDL that lead to stimulation of LDL oxidation and plaque formation. Dysfunctional HDL can further exacerbate LDL metabolic abnormalities and increase the risk of cardiovascular disease [52]. Also, our result showed a signi cant negative correlation between FABP4 plasma levels with HDL and LDL levels in patients RA (r =-0.224, P = 0.085; r =-0.098, P = 0.454, respectively), which may re ect Dyslipidemia in these patients.…”
Section: Discussionsupporting
confidence: 51%
“…RA in ammation causes changes in the structure of HDL that lead to stimulation of LDL oxidation and plaque formation. Dysfunctional HDL can further exacerbate LDL metabolic abnormalities and increase the risk of cardiovascular disease [52]. Also, our result showed a signi cant negative correlation between FABP4 plasma levels with HDL and LDL levels in patients RA (r =-0.224, P = 0.085; r =-0.098, P = 0.454, respectively), which may re ect Dyslipidemia in these patients.…”
Section: Discussionsupporting
confidence: 51%
“…Prior research has shown that fruits and vegetables are crucial for maintaining good health due to their nutrient content and anti-inflammatory properties ( 45 ). Consuming fresh fruits and vegetables is beneficial in RA and may be related to the fact that macronutrients and micronutrients modulate the pathogenesis of RA by regulating the migration and activity of neutrophils ( 46 ). However, our study did not find a causal association between the two, and even in the PsA causal association study, we found Fresh fruit intake as a risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Different micronutrients relate to neutrophil biology in homeostasis and disease states ( 174 ), in particular, Vitamin C ( 175 178 ), iron ( 179 181 ), zinc ( 182 185 ), Vitamin D ( 186 , 187 ) and Vitamin A ( 188 , 189 ). In general, a deficiency in any one of these micronutrients is associated with dysregulated neutrophil functions, particularly neutrophil recruitment, degranulation, ROS formation and NETosis, resulting in higher susceptibility to recurrent and severe infections.…”
Section: Regulation Of Neutrophil Functions In Various Nutrient Envir...mentioning
confidence: 99%